Contaminant and Environmental Influences on Thyroid Hormone Action in Amphibian Metamorphosis - Thambirajah, Anita A.; Koide, Emily M.; Imbery, Jacob J.; Helbing, Caren C. (Frontiers in Endocrinology, 2019)
Aquatic and terrestrial environments are increasingly contaminated by anthropogenic sources releasing industrial and agricultural chemicals including pesticides, pharmaceuticals and personal care products. Many of these substances have the potential to disrupt endocrine function, yet thyroid hormone (TH) action has garnered relatively little attention. Anuran postembryonic metamorphosis is strictly dependent on TH and perturbation of this process can serve as a sensitive barometer for the detection and mechanistic elucidation of TH disrupting activities of chemical contaminants and their complex mixtures. The ecological threats posed by these contaminants are further exacerbated by changing environmental conditions such as temperature, photoperiod, pond drying, food restriction, and ultraviolet radiation. We review the current knowledge of several chemical and environmental factors that disrupt TH-dependent metamorphosis in amphibian tadpoles as assessed by morphological, thyroid histology, behavioral, and molecular endpoints. Although the molecular mechanisms for TH disruption have yet to be determined for many chemical and environmental factors, several affect TH synthesis, transport or metabolism with subsequent downstream effects. As molecular dysfunction typically precedes phenotypic or histological pathologies, sensitive assays that detect changes in transcript, protein, or metabolite abundance are indispensable for the timely detection of TH disruption. The emergence and application of genomics-based techniques – transcriptomics, proteomics, metabolomics, and epigenomics – on metamorphosing tadpoles are powerful emerging assets for the rapid, proxy assessment of toxicant or environmental damage for all vertebrates including humans. Moreover, these highly informative genomics techniques will complement morphological, behavioral, and histological assessments, thereby providing a comprehensive understanding of how TH-dependent signal disruption is propagated by environmental contaminants and factors.